A Typology of Ethical Issues to Better Support the Development of Ethical Sensitivity Among Healthcare Professionals - Drolet, Marie-Josée (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2024)
For many healthcare professionals, identifying the ethical issues arising from their professional practice can be a challenge, for a variety of reasons. This paper presents a typology of six different types of ethical issues that can support the development of healthcare professionals’ ethical sensitivity, i.e., their ability to identify ethical issues encountered in their day-to-day practice. In addition to defining each of these issues, i.e., ethical blindness, myopia, dilemma, temptation, silence, and distress, examples are given and possible solutions proposed.